The phenotypic characteristics of polymorphonuclear neutrophils and their correlation with B cell and CD4+T cell subsets in thyroid-associated ophthalmopathy - Jin, Ke; Yao, Qian; Sun, Bin (Frontiers in Immunology, 2024)
Introduction Thyroid-associated ophthalmopathy (TAO) is considered to be an organ-specific autoimmune disease. Polymorphonuclear neutrophils (PMN) have been implicated in the pathogenesis of TAO. However, little is known about the role of PMN in the development of TAO, much less the relationship between PMN with B cells and CD4+T cells in TAO. Objective This study aims to investigate the phenotypic characteristics of PMN and the relationship between PMN with CD4+T cell and B cell subsets in the pathogenesis of TAO. Methods Blood routine information was collected from 135 TAO patients, 95 Grave’s disease without TAO (GD) patients, and 116 normal controls (NC), while surface marker expression of PMN and the level of CD4+T cell and B cell subsets in peripheral blood from 40 TAO patients, 17 GD patients, and 45 NC was assessed by flow cytometry. Result The level of PMN, CD62L+PMN, CD54+PMN, CD4+T cells, and Th17 cells displayed an increase in TAO patients than NC, while Treg cells were lower in the TAO group compared to NC. There was no statistical difference in Th1 and plasma cells among the groups. PMN were positively correlated with Th17 cells, but not the Th1, Treg, and plasma cells. Conclusion In the present study, we found that the percentage of PMN and PMN subset cells was significantly higher in TAO than in NC, and PMN were positively correlated with Th17 cells. It suggests that PMN may be involved in the immunopathogenesis of TAO and modulate the Th17 cell response during this process.